The Effect of Profitability, Liquidity, and Leverage on Financial Distress with Company Size as a Moderating Variable in Infrastructure, Utility, and Transportation Companies Listed on the Indonesia Stock Exchange from 2019 to 2023 - Kevin Kristorio; Eva Wany; Indahwati Indahwati (Jurnal Indonesia Sosial Sains, 2025)
Financial distress is a critical issue affecting companies, particularly in the infrastructure, utility, and transportation sectors, which require substantial capital investment. Various factors, including profitability, liquidity, and leverage, influence financial distress, while company size may play a moderating role. Understanding these factors is crucial for corporate decision-makers and investors to mitigate risks and enhance financial stability. This reseach aims to analyze the effect of profitability, liquidity, and leverage on financial distress, with company size as a moderating variable in infrastructure, utility, and transportation firms listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. The research adopts a quantitative approach, utilizing secondary data obtained from audited financial statements of 30 selected companies over five years (2019–2023), resulting in 150 observations. The study employs SmartPLS version 4 for data analysis, including descriptive statistical tests, measurement model evaluations, and hypothesis testing through bootstrapping. The findings reveal that profitability and liquidity have a significant positive effect on financial distress, while leverage has a significant negative effect. Furthermore, company size moderates the relationship between liquidity and financial distress but does not moderate the effects of profitability and leverage on financial distress. The research concludes that effective financial management, particularly in maintaining profitability and liquidity, is essential in reducing financial distress. Additionally, company size plays a critical role in strengthening liquidity's impact on financial distress. These findings provide theoretical contributions to financial literature and practical implications for corporate financial management and investment decision-making.